Global Insights: People & Cultures - Hantula, James Neil; Hantula, James Neil; Flickema, Thomas O.; Farah, Mounir A.; Karls, Andrea Berens; Johnson, Ellen C.K.; Thuermer, Katherine A.; Resnick, Abraham; Kane, Paul W. (Columbus, Ohio: Merrill Publishing Company, 1980)
The intent of Global Insights is to provide that knowledge and understanding by having the peoples of eight different geographical regions speak for themselves about the elements that have shaped their lives and made them the way they are today.
includes glossary and index.
English text.